2017
DOI: 10.3346/jkms.2017.32.2.303
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Presence and Severity of Diabetic Ketoacidosis at Diagnosis of Type 1 Diabetes in Korean Children and Adolescents

Abstract: The aim of this study was to identify the risk factors for presence and severity of diabetic ketoacidosis (DKA) at the onset of type 1 diabetes mellitus (T1DM) in Korean children and adolescents. A retrospective chart review of children and adolescents newly diagnosed with T1DM was conducted in seven secondary and tertiary centers in Korea. Eligible subjects were < 20 years of age and had records on the presence or absence of DKA at the time of T1DM diagnosis. DKA severity was categorized as mild, moderate, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 23 publications
3
21
0
Order By: Relevance
“…Secondly, age-related differences in the frequency of DKA at T1D onset was observed in this study, subsequently, almost half of children aged 0-4 developed DKA, as opposed to older individuals who had a lower prevalence of DKA. Comparable high frequency of DKA in younger children with new-onset diabetes was reported from other studies worldwide [7,9,10,12]. It seems to be important, because common signs of T1D often resemble symptoms of other disease.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Secondly, age-related differences in the frequency of DKA at T1D onset was observed in this study, subsequently, almost half of children aged 0-4 developed DKA, as opposed to older individuals who had a lower prevalence of DKA. Comparable high frequency of DKA in younger children with new-onset diabetes was reported from other studies worldwide [7,9,10,12]. It seems to be important, because common signs of T1D often resemble symptoms of other disease.…”
Section: Discussionmentioning
confidence: 64%
“…Diabetic ketoacidosis (DKA), one of the most life-threatening severe T1D complications, is highly prevalent in newly diagnosed pediatric patients and its frequency at diagnosis varies from 12.8% to 80% depending on a geographic location [7]. Moreover, younger children, aged < 5 years, are at greater risk of developing DKA [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A low level of maternal education was associated with a higher risk of DKA in 401 children under 15 years of age in Lithuania (18) while in a series of 474 children under 17 years of age in Poland an association between delayed diagnosis of type 1 diabetes and level of maternal education (19) was not found. Likewise, in a study conducted in Korea, no association was found between the level of parental education and the risk of DKA in a group of 361 children, however, the children of parents with low education showed an increased risk of severe DKA (20).…”
Section: Parental Education and Occupational Levelsmentioning
confidence: 87%
“…Approximately 10~70% of these patients experience DKA [14], which, in children, Factors that contribute to the incidence of DKA include poorly metabolic control [16] and a rapid decrease in pancreatic beta cell function [17]. In a recent study, age under 12 years, lower serum C-peptide level, preceding infection, and delayed diagnosis were strongly related to DKA; and severe DKA was increased in situations where there was limited parental education level and a prior episode of infection [18].…”
Section: Discussionmentioning
confidence: 99%